2004
DOI: 10.1144/jm.23.1.15
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomic and distributional survey of marine benthonic Ostracoda off Kerguelen and Heard Islands, South Indian Ocean

Abstract: -From an examination of 34 grab and dredge samples ranging from 110 m to 3584 m water depth, collected during Eltanin cruise 47 across the Kerguelen Plateau, 26 shallow-water and 35 deep-sea benthonic ostracod species have been identified. Systematic notes and illustrations of the common and some of the rare species are presented. Two new species are described: Philoneptunus cassidyi n. sp. and Taracythere abyssora n. sp. Comparisons made with the Atlantic and SW Pacific Oceans and circumAntarctic regions indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 26 publications
5
40
0
1
Order By: Relevance
“…Species of Krithe have different depth distributions ranging from b500 to N5000 m (Rodriguez-Lázaro and , but previous studies have shown that the genus is mainly associated with cold water masses (Coles et al, 1994;Cronin et al, 1994Cronin et al, , 1999Whatley et al, 1996;Ayress et al, 1997;Rodriguez-Lázaro and Cronin, 1999;Ayress et al, 2004). Instances when Krithe is found living in relatively shallow water are usually in high-latitude seas, the Arctic Ocean (Cronin et al, 1994Whatley et al, 1998), in very cold AAIW off the Kerguelen Plateau, South Indian Ocean (Ayress et al, 1997) and/or in areas of coastal upwelling (Rodriguez-Lázaro and .…”
Section: Ecological Aspects Of the Ostracod Faunamentioning
confidence: 99%
See 2 more Smart Citations
“…Species of Krithe have different depth distributions ranging from b500 to N5000 m (Rodriguez-Lázaro and , but previous studies have shown that the genus is mainly associated with cold water masses (Coles et al, 1994;Cronin et al, 1994Cronin et al, , 1999Whatley et al, 1996;Ayress et al, 1997;Rodriguez-Lázaro and Cronin, 1999;Ayress et al, 2004). Instances when Krithe is found living in relatively shallow water are usually in high-latitude seas, the Arctic Ocean (Cronin et al, 1994Whatley et al, 1998), in very cold AAIW off the Kerguelen Plateau, South Indian Ocean (Ayress et al, 1997) and/or in areas of coastal upwelling (Rodriguez-Lázaro and .…”
Section: Ecological Aspects Of the Ostracod Faunamentioning
confidence: 99%
“…Some species are restricted to shallow subpolar shelves, others inhabit the upper continental slope and Central Arctic Ocean (Whatley and Masson, 1979;Brouwers, 1994;Cronin et al, 1995;Whatley et al, 1996Whatley et al, , 1998Ayress et al, 2004;Stepanova et al, 2004;Stepanova, 2006). Cytheropteron species from the Arctic Ocean are usually found in the deep North Atlantic, N1000 m (Whatley and Coles, 1987;Dingle and Lord, 1990;Van Harten, 1990;Cronin et al, 1996Cronin et al, , 1999.…”
Section: Ecological Aspects Of the Ostracod Faunamentioning
confidence: 99%
See 1 more Smart Citation
“…Though the wide temporal range ascribed to those two species (Oligocene to Recent) might be questionable (see discussion in Bergue et al, 2013) the data provided by Yasuhara and colleagues support that the circum-Antarctic dispersion had already been stablished at least in the Neogene, even before the complete opening of the Drake Passage. Ayress et al (2004) also proposed that the Southern Ocean and its ACC are responsible for the establishment of dispersion routes for ostracodes. Based on the paleobathymetric interpretation by Gomide (1989) of the deposits here studied (outer shelf/ upper slope) they are in accordance to the bathymetric preferences of other species of Inversacytherella, such as I. tanantia and I. pleistocenica, which were also described in deep waters.…”
Section: Discussionmentioning
confidence: 99%
“…Ocean circulation and hydrologic changes, productivity and sedimentary processes are examples of research fi elds that have benefi ted from the study of ostracodes (Cronin, 1983;Ayress et al, 2004;Yasuhara & Cronin, 2008).…”
Section: Introductionmentioning
confidence: 99%